THE USE OF CROSSWORD PUZZLES TO INCREASE STUDENTS' VOCABULARY MASTERY - Ramli; Usman, Sriati; Anggreni, Afrillia (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aims to determine whether the use of Crossword Puzzles can increase Vocabulary of SMP Alkhairaat Tandaigi. This is research using a quasi-experimental research design. In selecting the sample, the researcher used a purposive sampling technique. The research samples were class VIII A as an experimental group and class VIII B as a control group. The instrument of data collection was divided into a pretest and a posttest. The data gathered were analyzed statistically. The results of the data analysis show that the mean score of both tests where the mean score of the experimental group improved from 63.93 to 73.33, and the control group's mean score improved from 63.17 to 68.56. The result showed that the value of t-counted (2.176) was greater than the value of the t-table (1.683) by applying a 0.05 level of significance and the degree of freedom (df) 22+21-2= 41. It could be concluded that the research hypothesis is accepted. In other words, Crossword Puzzles could increase vocabulary of grade VIII students at SMP Alkhairaat Tandaigi.